Pengaruh Tingkat Margin Terhadap Keputusan Pengambilan Pembiayaan Murabahah Pada BPRS Gajahtongga Kotopiliang Kota Sawahlunto - Eliza Eliza (Universitas Dharma Andalas, 2019)
ABSTRACK This study was conducted to find out more about the effect of margin level on the decision to take murabahah financing at BPRS Gajahtongga Kotopialang, Sawahlunto City with the aim of assessing the effect of these two variables, namely margin level as independent and murabahah financing decision making is dependent. The results obtained are from the two variables, partially or simultaneously giving a positive and significant influence, where the significance value of the F-test and t-test compared to alpha is smaller (0.023 <0.05), meaning the margin level greatly influences the decision making murabahah financing.